Analysis for Yangmingtan Bridge collapse. (October 2015) - Fan, Yunxiao; Zhu, Jing; Pei, Jingjing; Li, Zhi; Wu, Yanguang
Highlights: More bridge accidents have occurred in China, but few accidents were tracked. Accident information were forgotten because of lack of investigation report. NVivo software package was adopted to organize accident information. Rasmussen's accident causation model was adopted as the frame nodes. The research shows the effectiveness in exposing the accident contributors. Abstract: In recent years, more than thirty bridge accidents have occurred in China, but only few accidents were tracked and most accident investigation reports were not open to the public. The Yangmingtan Bridge collapse accident occurred on 24 August, 2012 in Harbin City, which caused three fatalities and five injuries. This accident has evoked wide concern from the public and media, but no official report provided any conclusion on the cause of the accident until now, while no related research was ever undertaken either. NVivo is a qualitative data analysis package which helps researchers to organize and analyze complex non numerical or unstructured data. Because of the lack of data in the official report, this research collected both texts and multimedia information from the web, newspaper and videos to identify potential root causes of the accident. This research first organized all information with the aid of NVivo 8.0 software. Then Rasmussen's accident causation model was adopted for use as the frame nodes for the case study. Based on the software, this research analyzed the system wide failures and actions involved in the accident and identified the multi-levels of failure modes which included government, regulatory agency, company, management, staff, and the physical accident sequence.